Blood type susceptibility to SARS-CoV-2 at a tertiary hospital in Accra, Ghana - Prince N. Odoom; Olayinka S. Okoh; Yaa Y. Asare; Clara O. Mac-Arthur; Judith D. Azumah; Albert Mensah; Akua K. Yalley; Kwamena W. Sagoe; Nicholas I. Nii-Trebi (Microbiology Spectrum)
ABSTRACT Pandemics from viral outbreaks, such as that caused by SARS-CoV-2, have significant impacts worldwide. The factors that underlie differential susceptibility to severe COVID-19 outcomes are not fully understood. The role of the ABO blood group in the outcome of SARS-CoV-2 infections remains to be clarified in different populations. This study described the SARS-CoV-2 seroprevalence and examined the association of the ABO blood group with COVID-19 disease among apparently healthy and COVID-19 patients at the Korle Bu Teaching Hospital, Accra. The study involved 277 participants comprising 200 healthy individuals and 77 PCR-confirmed COVID-19 patients with mild or severe symptoms. Anti-SARS-CoV-2 antibody assay (IgM/IgG) was performed, and ABO blood grouping was done on plasma samples using the reverse blood grouping method. Statistical analyses were performed in R for the association of socio-demographic parameters and ABO blood groupings of participants with SARS-CoV-2 infection status. The total SARS-CoV-2 seropositivity was 61.4% (157/277). Most of the participants (245/277, 88.4%) were unvaccinated. Of the 245 unvaccinated individuals, 127 (51.8%) were IgG reactive. A significant association was observed between ABO blood group and COVID-19 disease status. Antigen A participants had a higher probability of symptomatic infection than non-antigen A individuals. Blood group O appeared more protective than other blood types among the participants. Seropositivity was high among the participants studied—vaccinated and unvaccinated. Blood group A is associated with an increased risk of COVID-19, whereas blood group O appears protective. Further studies involving larger sample sizes are required to confirm these findings.IMPORTANCEThe transmissibility and virulence of SARS-CoV-2 and the severity of COVID-19 disease appeared to vary across nations and among populations. However, the factors that account for the differential susceptibility and COVID-19 outcomes are not well understood. The roles of host immune defense mechanisms and genetic makeup have been implicated. This study investigated the seroprevalence of anti-SARS-CoV-2 antibodies (IgM and IgG) in apparently healthy individuals and COVID-19 patients; using a reliable but inexpensive blood group typing based on direct hemagglutination technique and rigorous statistical analyses, we determined the association of ABO blood groups with COVID-19 disease. We found appreciably high seropositivity among the participants studied—both vaccinated and unvaccinated—and showed that blood type significantly influences SARS-CoV-2 infection and COVID-19 severity, with blood group A associated with severe COVID-19 disease, whereas blood group O appears protective. Further studies involving a larger sample size are required to confirm these findings.